Pathogenic roles of follicular helper T cells in IgG4-related disease and implications for potential therapy - Xu, Jingyi; Zhai, Jiayu; Zhao, Jinxia (Frontiers in Immunology, 2024)
IgG4-related disease (IgG4-RD) is a recently described autoimmune disorder characterized by elevated serum IgG4 levels and tissue infiltration of IgG4+ plasma cells in multiple organ systems. Recent advancements have significantly enhanced our understanding of the pathological mechanism underlying this immune-mediated disease. T cell immunity plays a crucial role in the pathogenesis of IgG4-RD, and follicular helper T cells (Tfh) are particularly important in germinal center (GC) formation, plasmablast differentiation, and IgG4 class-switching. Apart from serum IgG4 concentrations, the expansion of circulating Tfh2 cells and plasmablasts may also serve as novel biomarkers for disease diagnosis and activity monitoring in IgG4-RD. Further exploration into the pathogenic roles of Tfh in IgG4-RD could potentially lead to identifying new therapeutic targets that offer more effective alternatives for treating this condition. In this review, we will focus on the current knowledge regarding the pathogenic roles Tfh cells play in IgG4-RD and outline potential therapeutic targets for future clinical intervention.